Single-stage Total Cranial Vault Remodeling for Correction of Turricephaly: Description of a New Technique. Issue 8 (August 2018) - Rottgers, Stephen Alex; Ganske, Ingrid; Citron, Isabelle; Proctor, Mark; Meara, John G.
Abstract : Background: Turricephaly is considered one of the most difficult cranial deformities to correct as addressing cranial height can result in increased intracranial pressure. We describe a new technique of total calvarial remodeling with bony transposition to simultaneously correct turricephaly and brachycephaly while preserving intracranial volume. Methods: A retrospective review of patients undergoing single-stage cranial vault remodeling by a single surgeon (J.G.M.) at a single center between 2007 and 2015 was performed. The procedure consists of a frontal bandeau followed by a 1 cm 360 o axial strip craniectomy. The strip is then rotated 90 degrees into a coronal orientation and interposed between fronto-parietal and parito-occipital segments. Modification for occipital widening can also be performed. Results: Six patients with turribrachycephaly underwent the procedure over the 8-year period. Four patients were operated at less than 1 year of age, one patient underwent surgery at 2 years, and one at 9 years. Mean operative time was 4 hours, and mean transfusion was 300cc. There were no major complications. Mean cranial height reduction achieved was 1.6 cm (range, 1.0–2.0 cm), and mean anterior–posterior expansion was 3.4 cm (range, 2.3–4.5 cm). Patients also showed improvement in supraorbital retrusion. Conclusion: Single-stage cranial vault remodeling with axial strip craniectomy and coronal interposition is safe and allows for simultaneous correction of turricephaly and brachycephaly while preserving intracranial volume.